2023
DOI: 10.3389/fnagi.2023.1161678
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent theta burst stimulation attenuates oxidative stress and reactive astrogliosis in the streptozotocin-induced model of Alzheimer’s disease-like pathology

Abstract: IntroductionIntracerebroventricularly (icv) injected streptozotocin (STZ) is a widely used model for sporadic Alzheimer’s disease (sAD)-like pathology, marked by oxidative stress-mediated pathological progression. Intermittent theta burst stimulation (iTBS) is a noninvasive technique for brain activity stimulation with the ability to induce long-term potentiation-like plasticity and represents a promising treatment for several neurological diseases, including AD. The present study aims to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…This activation could reduce the damage caused by oxidative stress and protect brain tissue. Consistent with these findings, our previous studies have shown that Nrf2 is increased after iTBS treatment [21]. Furthermore, brain-derived neurotrophic factor (BDNF), which is known for its role as a modulator of synaptic plasticity, has been shown to induce the nuclear translocation of Nrf2.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This activation could reduce the damage caused by oxidative stress and protect brain tissue. Consistent with these findings, our previous studies have shown that Nrf2 is increased after iTBS treatment [21]. Furthermore, brain-derived neurotrophic factor (BDNF), which is known for its role as a modulator of synaptic plasticity, has been shown to induce the nuclear translocation of Nrf2.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, brain-derived neurotrophic factor (BDNF), which is known for its role as a modulator of synaptic plasticity, has been shown to induce the nuclear translocation of Nrf2. In our previous study, we found an increased protein expression of BDNF after 21 days of iTBS stimulation in 6-OHDA-induced PD [21,23]. Collectively, these factors could contribute to the observed enhancement in the general state of oxidative balance.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations